The revenue structure of Olutanga, Zamboanga del Sur its implication to improved fiscal administration, 1986-1990 - Tago, Estita R.C
This study was primarily undertaken by the researcher to asses the revenue structure of the municipality of Olutanga, Zamboanga del Sur, covering the calendar years 1986 to 1990 and at the same time to know the strength and weaknesses in relation to an improved fiscal administration. This study sought to answer the following questions : 1) what are the sources of revenue that accrue to the General Fund, Infrastructure Fund andd Special Educational Fund of the municipality? 2) what are the expenditures of the municipality? 3) how were funds appropriated in different projects? 4) how do the funds and projects for the year 1986 to 1990 compare?. The researcher utilized the the descriptive survey method in conducting this research. The data were gathered through unstructured interviews and documentary analysis of available materials, rules documents and records of the Municipal Treasurer's Office as well as well as with the circuit municipal auditor of Oluntanga, Zamboanga del Sur. The findings of the study were the following : 1) Based on the data gathered, by the researcher, the major sources of income of the municipality were the following : (a) tax revenue, (b) operating and miscellaneous revenue, and (c) grant-in-aids. That the tax revenue are divided into three funds as the general fund, infrastructure fund and special educational fund, composing of (a) other taxes, (b) income from government business operating and grant-in-aids. 2. That the three major expenditures are Personal Services, maintenance and other Operating expenses and Capital Outlay. 3. That in 1986, the Municipality of Olutanga has realized an income of ₱690,417.47 in all funds out of the estimated income of ₱677,294.97. This revenue was lowered by 1.91% compared to the calendar year 1985 in the amount of ₱703,860.98 which recorded a decrease of ₱13,443.51. Although, the infrastructure fund posted a decrease of ₱50,711.69, however, this was off-set by an increase of ₱34,519.26 or 6.82% in the general fund, and by ₱2,748.92 or 20.89% in the Special Educational Fund (SEF). 4.Of the total income during 1986, tax revenue represent 73.92% or ₱510.343.86 of which 6.63% of ₱33,829.16 were collections of real property tax ; 13.35% or ₱68,115.60 came from taxes on goods and services; and 80.02% or ₱408,399.20 came from other taxes of which ₱387.505.43 are local government share on internal revenue collections. 5. That the total realized income of the municipality rose from last year's ₱690,417 to ₱756,625.55 in 1987 out of the estimated income of ₱684,945.72. An increase of ₱66,208.08 or 9.57% as compared to last year's decrease of ₱13,453.51. The increase could be attributed to the municipality's higher collections target in the Revenue and Operating and Miscellaneous Income. although the total increase from these two (2) sources had amounted to ₱85,102.99, however, this was off-set by the decrease in the grant-in aids in the amount of ₱14, 740.66. 6. That of the total income realized, tax revenue represent 74.87% or ₱566.257.00 of which 5.15% or ₱29,166.38 came from collections of real property taxes, 12.54% or ₱71,001.94 came from taxes on goods and services; and 82.31% of ₱466.088.68 came from other taxes of which ₱447,854.29 are local government share on internal revenue collections. 7. That in calendar year 1988, the municipality realized an income of ₱1, 393,817.04 in all funds out of its estimated in the amount of ₱916, 214.88. It records an increase of ₱637,191.49 or 45.71% as compared to last year's income of ₱756,625.55. The increase was attributed by the inclusion of the grant-in-aids Nalgu funds. 8. That of the total revenue realized, tax revenue represents 54.16% or ₱754, 896.49 of which 3.99% or ₱30, 118.91 came from collections of real property taxes: 11.21% or ₱84,650.65 came from taxes on gods and services: and 84.80% or ₱640,126.93 came from other taxes of which ₱621,612.10 are local government share on internal revenue collections, and specific tax allotments. 9. That for calendar year 1989, out of the estimated income of ₱981, 831.61, its realized income is ₱1, 534, 935.32 as compared to last year's ₱1, 393,817.04 or an increase of ₱141,108.28 or 10.12%. 10. That of the total income, tax revenue represents 63.88% or ₱980,459.48 of which ₱30, 605.29 came from real property tax collections; ₱87, 131.50 came from taxes on goods and services; and ₱862,722.69 came from other taxes, of which ₱834,150.70 pertained to local government shares on internal revenue and specific tax allotments. 11. That the total income realized for calendar year 1990, out of the estimated income of ₱1,175,500.82, the municipality realized an income of ₱2,022,067.94 as compared to last year's ₱1,534,925.32 or an increase of ₱487,142.62 or 31.74%. 12. That of the total income realized, tax revenue represents 71.04% or ₱1,436,415.52 of which ₱63,467.35 came from real property tax collections; ₱99,835.45 came from taxes on goods and services; and ₱1, 372,948.18 came from other taxes of which ₱1, 243,958.00 pertained to local government shares on Internal Revenue and Specific Tax Allotments. 13. That for the last five years, the income of the municipality had been continuously registering an upward trend. 14. That corresponding to the economic growth and social development, the expenditures of the municipality followed the growth trend of its income. 15. That inspite of the recorded upward trend of income for the last five years, it could be noted that the municipality is still dependent on the revenue allotments dispite having collected more than what was estimated. 16. That the problems encountered by the municipality for the poor collection of taxes were due to the following reasons: (a) Failure of some taxpayer to pay their taxes (b)Failure of the municipal government authorities to tap other potential sources of revenue and to implement programs designed to create tax payment awareness to the residents. CONCLUSIONS - Based on the given findings, the researcher had drawn up the following conclusions: 1) The major sources of revenue of the municipality of Olutanga were the following: (a) Property taxes b) Taxes on goods and services c) Local taxes d) National Taxes (BIR allotments) e) Other taxes f) Operating and miscellaneous Income. The General Fund, Infrastructure Fund and Special Education Fund were the three funds that the revenue of the municipality accrue. 2) The municipality of Olutanga is heavily dependent on allotment from the national government through the share in the Bureau of Internal Revenue Taxes, collected from the municipality. 3) The actual collection exceeds by municipality is more than the estimated income. IMPLICATIONS: The findings obtained and the conclusions drawn in the study, suggest that there is a need to restructure the tax collections campaign of the municipality. In order that the development projects be adequately funded, the municipality must not rely solely on the allotments from the national government. The Municipal Treasurer's Office personnel are then expected to play a vital role in the effective revenue collection for the municipal government projects funding. RECOMMENDATIONS based on the findings and conclusion, the researcher wish to recommend the need to exert effort in the collection of taxes and income to the municipality. The the Municipal assessors Office shall inspect physically all the properties Occupied by the government agencies and make adjustments of the records and count the corresponding taxes due to the municipality. The revenue collection clerks must be given an area of responsibility, properly identified and be reshuffled on a quarterly basis, and encourage further researcher and similar studies on fiscal administration on other municipalities, cities in Mindanao Region.